The Influence of Competence, Experience and Work Environment on Employee Performance - Irwan Usman (Jurnal Economic Resource, 2021)
This study aims to analyze and investigate the impact of competence, experience, and work environment on Inspectorate of Makassar City employees performance. The parties involved in the Makassar City Inspectorate employees' performance, a total of 66 people, were the study's target population. Using multiple linear regression analysis models, they all became respondents. This study's findings show that competency, experience, and work environment variables all positively and significantly impact Makassar City Inspectorate Employees' performance. While only partially, the competency factor has the most significant impact on the Inspectorate of Makassar City Employees' performance. According to this study's findings, Makassar City Inspectorate employees should pay more attention to factors that can improve employee performance, such as human resource development through education and training, and create a more conducive work environment.